Status and associated factors of food and nutrition literacy among young adults aged 15–44 years in Shenzhen City, China - Zhixue, Li; Ying, Xu; Zheng, Liu; Yan, Ma; Yanfang, Guo; Dewang, Wang; Weijun, Yu; Rencheng, Zhao; Qing, Yuan; Meihong, Xu (Frontiers in Public Health, 2024)
Background Food and nutrition literacy (FNL) plays an important role in young adults’ dietary habits and nutrition. This study aimed to investigate FNL status and its associated factors among young adults aged 15–44 years in Shenzhen. Methods A cross-sectional survey of 5,390 participants was conducted in June 2021. FNL was measured using the Food and Nutrition Literacy Questionnaire for Chinese Adults (FNLQ). A generalized linear model was employed to analyze the factors associated with FNL. Results The median FNL score (total score = 100) was 68.00, which was below the adequate level of 80. FNL was divided into the two different domains of knowledge and skills, with significantly different scoring rate of 85.30 and 67.77%, respectively. The overall proportion of respondents with adequate FNL was 19.52%. The FNL score was significantly higher among the participants who were female (β = 2.665; 95% confidence interval [CI]: 2.031–3.299) and with higher education levels (β ranging from 5.632 [CI: 3.845–7.419] to 10.756 [CI: 8.973–12.538]), healthcare-related work experience (β = 4.197; CI: 3.557–4.837) and a higher economic status (β ranging from 0.753 [CI: 0.079–1.426] to 6.217 [CI: 5.208–7.227]). Those who were divorced or with an unknown marital status (β = −8.438; CI: −9.701, −7.175), abnormal body mass index (thin [β = −2.115; CI: −3.063, −1.166], overweight [β = −1.427; CI: −2.254, −0.600]), and suffering from chronic diseases (single disease [β = −3.483; CI: −4.485, −2.480], multimorbidity [β = −5.119; CI: −5.912, −4.327]) had significantly lower FNL scores. Conclusion Generally, the level of FNL among young adults in Shenzhen, China, was relatively low. Thus, nutrition education programs targeted at promoting improved FNL status call for additional emphasis, especially in subgroups with lower scores.